PENGARUH PERSEPSI HARGA, KUALITAS PRODUK DAN PENGALAMAN PELANGGAN TERHADAP KEPUASAN PELANGGAN NASI BORAN DI KABUPATEN LAMONGAN: ( Studi Pada Pelanggan Nasi Boran Di Kabupaten Lamongan) - Evi Rohmawati; Estik Hari Prastiwi (CV SWA Anugrah, 2024)
This research aims to analyze the influence of perceived price, product quality and customer experience on customer satisfaction with boran rice in Lamongan district. The type of data used is quantitative data. The sampling technique used in this research is purposive sampling with 100 respondents. The analysis used is regression analysis. multiple t test and f test. The results of this research show that the price perception variable has a significant effect on customer satisfaction. Product quality is not significant on customer satisfaction and customer experience has a significant effect on customer satisfaction and customer satisfaction has a significant effect on boran rice in Lamongan district.influence purchase decision after the closure of the TikTok Shop. The determination results of all independent variables (Content Marketing, Celebrity Endorser, Live Streaming) contributed 23.3% to the dependent variable (Purchase Decision) and the remaining 76.7% was influenced by other variables not included in the research